The impact of dividend policy on shareholders' wealth : evidence from the Vector Error Correction Model - De Wet, Johannes H.v.H. (Johannes Hendrik van Heerden) (University of Pretoria, 2013)
Dissertation (MCom (Financial Management Science))--University of Pretoria, 2012.